2020
DOI: 10.1590/scielopreprints.114
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Knowledge, Attitudes and Practices of Mozambican Public Employees in relation to the Prevention of COVID-19

Abstract: In the middle of December 2019, COVID-19 appeared in the Chinese City of Wuhan. It is a pathology that quickly spread around the world, counting, until the completion of the present study, with more than 2 million infected and about 140 thousand dead. The aim of the present study was to analyze knowledge, attitudes and practices of public workers from Mozambique on the prevention of COVID-19. To this end, 126 public workers in Mozambique (79 men, 43 women and 4 who chose not to disclose their gender) answered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Our findings is consistent with a study involving public workers in Mozambique conducted in the initial public health emergency declaration in March 2020, which showed that a large proportion of participants changed their routines, having remained confined at home to avoid exposure and contraction of the disease. 22 Findings from our study are also in line with another study carried out in Nepal reporting that human mobility patterns as a measure of prevention behavioral responses during the COVID-19 pandemic was significantly reduced during the first wave of COVID-19. 23 This was notable when people started to be confined to their homes to avoid exposure to COVID-19 in the streets, stopped traveling to and from work (primarily through crowded transport) and stopped engaging in non-essential shopping.…”
Section: Discussionsupporting
confidence: 90%
“…Our findings is consistent with a study involving public workers in Mozambique conducted in the initial public health emergency declaration in March 2020, which showed that a large proportion of participants changed their routines, having remained confined at home to avoid exposure and contraction of the disease. 22 Findings from our study are also in line with another study carried out in Nepal reporting that human mobility patterns as a measure of prevention behavioral responses during the COVID-19 pandemic was significantly reduced during the first wave of COVID-19. 23 This was notable when people started to be confined to their homes to avoid exposure to COVID-19 in the streets, stopped traveling to and from work (primarily through crowded transport) and stopped engaging in non-essential shopping.…”
Section: Discussionsupporting
confidence: 90%